Effectiveness of OCCIE Learning Model to Improve Science Process Skills of Senior High School Students - Marjuki Marjuki (Universitas Negeri Surabaya, 2022)
The research aims to analyze the effectiveness of the OCCIE learning model to improve the science process skills of high school students in learning chemistry. The OCCIE learning model has 5 phases, namely: Orientation, Construct, Communicate, Improve, and Evaluate which are specifically designed to improve science process skills. Methods of data collection using tests. The scientific process skills assessment instrument was valid and reliable. The main results show that the OCCIE learning model is proven to be effective in improving science process skills in learning chemistry in high school. In addition, there was a significant and consistent increase in the science process skills of Senior High School students in chemistry learning. The implications of the results of this study indicate that this model deserves to be used as an alternative model for Senior High School students' science process skills in chemistry learning in Indonesia. Further research can be focused on: (1) Teachers must prepare and ensure tools and materials can be used for experimental activities in the laboratory; (2) The time allocation must be adjusted to the characteristics of the material and students for those who are using the OCCIE Learning Model for the first time; (3) The group must have been determined by the teacher before learning using the OCCIE Learning Model so that the time allocation is more effective.